2008
DOI: 10.1016/j.neuroimage.2007.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex signals the requirement to break inertia when switching tasks: A study of the bivalency effect

Abstract: When switching tasks, if stimuli are presented that cue two of the tasks in the task set (i.e., bivalent stimuli), performance slowing is observed on all tasks, including those not cued by the bivalent stimulus. This slowing has been coined the bivalency effect, and may reflect adaptive tuning of the response style under conditions that appear to require adjustments in control over the course of action. Recent work on the function of the dorsal anterior cingulate (dACC) cortex has suggested that this neural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
66
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 45 publications
17
66
1
Order By: Relevance
“…As described in the section above on classic conflict monitoring, it was originally thought that within-trial conflict (incongruent and not congruent trials) activated the ACC, causing cognitive upregulation by way of the dorsolateral prefrontal cortex; i.e., increased cognitive control: see Botvinick et al, 2001;Botvinick et al, 1999;see Egner, 2007see Egner, , 2008, for reviews). However, recall that a legion of researchers have attempted to extend the role of the ACC beyond intratrial conflict (Botvinick et al, 2004;Brown & Braver, 2005;Rushworth et al, 2007;see Woodward, Metzak, Meier, &Holroyd, 2008, andHyafil, Summerfield, &Koechlin, 2009, for evidence of a distinct role for the ACC in task switching). One possibility, then, is that during task or language switching, there might be some amount of proactive interference (Philipp, Kalinich, Koch, & Schubotz, 2008) that would, because of the conflict between the current and previous representations, recruit the ACC.…”
Section: Classic Conflict Monitoringmentioning
confidence: 99%
“…As described in the section above on classic conflict monitoring, it was originally thought that within-trial conflict (incongruent and not congruent trials) activated the ACC, causing cognitive upregulation by way of the dorsolateral prefrontal cortex; i.e., increased cognitive control: see Botvinick et al, 2001;Botvinick et al, 1999;see Egner, 2007see Egner, , 2008, for reviews). However, recall that a legion of researchers have attempted to extend the role of the ACC beyond intratrial conflict (Botvinick et al, 2004;Brown & Braver, 2005;Rushworth et al, 2007;see Woodward, Metzak, Meier, &Holroyd, 2008, andHyafil, Summerfield, &Koechlin, 2009, for evidence of a distinct role for the ACC in task switching). One possibility, then, is that during task or language switching, there might be some amount of proactive interference (Philipp, Kalinich, Koch, & Schubotz, 2008) that would, because of the conflict between the current and previous representations, recruit the ACC.…”
Section: Classic Conflict Monitoringmentioning
confidence: 99%
“…Woodward, Metzak, Meier, and Holroyd (2008) contrasted univalent stimuli from a condition with purely univalent stimuli and univalent stimuli from a condition in which bivalent stimuli were occasionally intermixed on one of the tasks. The results showed that the bivalency effect was associated with activation in the dorsal anterior cingulate cortex (dACC), a brain area recruited for the adjustment of cognitive control (see Botvinick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The bivalency effect refers to the long-lasting performance slowing that occurs on univalent trials following bivalent stimuli, even on those univalent trials that share no overlapping features with the bivalent stimuli (e.g., Meier, Woodward, Rey-Mermet, & Graf, 2009;2014;Woodward et al, 2003;Woodward, Metzak, Meier, & Holroyd, 2008). The paradigm typically used to investigate this effect involves three blocks with regular switches between three tasks, such as a parity decision (odd vs. even), a color decision (red vs. blue), and a case decision (uppercase vs. lowercase; see Figure 1a).…”
mentioning
confidence: 99%
“…Moreover, it is associated with activation in the dorsal anterior cingulate cortex, a brain area recruited for the adjustment of cognitive control (Grundy, Benarroch, Woodward, Metzak, Whitman, & Shedden, 2013;Woodward et al, 2008) and it draws on memory resources because amnesic patients fail to show the typical pattern of a long-lasting performance slowing (Meier, Rey-Mermet, Woodward, Müri, & Gutbrod, 2013). …”
mentioning
confidence: 99%